2018
DOI: 10.1177/0734242x18790800
|View full text |Cite
|
Sign up to set email alerts
|

Households’ knowledge, attitudes, and practices toward solid waste management in suburbs of Phnom Penh, Cambodia

Abstract: This study developed logistic regression models to analyse the relationship between 12 observed variables on knowledge, attitudes, and practices toward solid waste management in the suburbs of Phnom Penh city. We interviewed 800 households, including 200 collection service users and 600 non-service users. The determinants of how individuals are aware of, think of, and behave were assessed in the models based on the values of estimated coefficient and probability of t-statistics. As a result, education level an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…Most residents in suburban areas complain to CINTRI for not providing services adequately, except for those areas with high beneficiaries. Evidently, similar findings are indicated in [20,35,37]. It can be seen that the public perception of PPP is important for explaining the reliability of services.…”
Section: Public Perceptionsupporting
confidence: 74%
See 3 more Smart Citations
“…Most residents in suburban areas complain to CINTRI for not providing services adequately, except for those areas with high beneficiaries. Evidently, similar findings are indicated in [20,35,37]. It can be seen that the public perception of PPP is important for explaining the reliability of services.…”
Section: Public Perceptionsupporting
confidence: 74%
“…Collection frequency was the most important factor affecting user satisfaction, especially in peri-urban areas. The recent study on knowledge, attitude, and practices of household waste management in suburbs of Phnom Penh indicated the situation of SWM is not satisfactory owing to the responses of 78.68% from within service using households and the collection frequency is 46.19% for twice a week and 22.34% for once a week [37]. Likewise, the study also indicated that the technical capacity and skills of LGAs is limited-they are not actually accepting their duty for management services in their respective areas.…”
Section: Quality Of Servicesmentioning
confidence: 99%
See 2 more Smart Citations
“…In Cambodia, in the capital city Phnom Penh, where the MSW management (MSWM) system lacks regulation, households commonly burned, buried, or dumped about 361,000 tons of MSW in 2008, and 635,000 tons in 2015 [40]. In Thailand, more than 60% of the SW final disposal was carried out by open dumping.…”
Section: Environmental and Social Issues Due To Sw Mismanagementmentioning
confidence: 99%